Solar drying - Belessiotis, V.; Delyannis, E.
Solar radiation use for drying is one of the oldest applications of solar energy. It was used since the dawn of mankind mainly for food preservation but also for drying other useful materials as cloths, construction materials, etc. The first installation for drying by solar energy was found in South France and is dated at about 8000 BC. Solar heat was the only available energy source to mankind until the discovery and use of wood and biomass. Until to day in remote small communities, not only in the so-called third world regions, but also in the western countries, people take advantage of solar radiation to dry and preserve small amounts of food. Solar drying has not yet widely commercialized. Solar dryers are equipment, generally of small capacity and based rather on empirical and semi-empirical data than in theoretical designs. The majority of the numerous solar dryer designs, which are available, are used mainly for drying of various crops either for family use or for small-scale industrial production. In this chapter on "Solar Drying" various direct and indirect solar drying applications and some of the numerous solar dryers are described. A very short historical description of solar drying through the centuries is also given. Some drying phenomena, independently of the type of energy used, and the general laws that govern drying methods by convection are shortly analyzed in order the reader to easily follow the details of the solar drying procedure. Special solar collectors used in drying and methods of coupling to the various solar dryers are described as an indirect solar thermal energy source. At the end an example of drying of grapes to produce black current raisins, by indirect solar radiation, is given as well.
Keywords: MOLLIER DIAGRAM; ECONOMICS OF SOLAR DRYERS; AGRICULTURAL CROP PRESERVATION; HOT BOX CHAMBER; GREENHOUSE DRYER ANALYSIS; SEMI-CYLINDRICAL PLASTIC DRYER